Regulation and Criminal Justice : Innovations in Policy and Research - Quirk, Hannah, 1973-; Seddon, Toby, 1970-; Smith, Graham, 1957- (Cambridge University Press, 2014)
"While regulatory institutions and strategies have been the subject of increasing academic attention, there has been limited application of regulatory theories to criminal justice scholarship. This collection of essays from a range of outstanding international scholars adopts a critical, inter-disciplinary approach, providing an innovative application of regulatory theory to the practice of criminal justice and offering suggestions for further research. Part I explores the aims and values of criminal justice and other regulatory networks and the synergies and tensions between these fields; Part II examines criminal justice as a regulatory force to control 'deviant' and anti-social behaviour and Part III examines the regulation and oversight of criminal justice through the operation of prison inspectorates and explores notions of responsive justice"--